-126=-2x-(4x+13

Simple and best practice solution for -126=-2x-(4x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -126=-2x-(4x+13 equation:



-126=-2x-(4x+13
We move all terms to the left:
-126-(-2x-(4x+13)=0

See similar equations:

| 15x=3(x-7) | | w•9=27 | | 2(3x-1)-5(x+4)=21 | | -88=-8(m+8) | | -3(-x+2)+4x+3=3 | | X+y×2=24 | | 2t-34=t | | 15-35x=155 | | p+25=3p+23 | | Y=-7x-29 | | x-(11)/5=(-6) | | 9w-27=20w-54 | | 2z+19=7z-51 | | -168=(-7)x-(7) | | 3n^2-18n+24=0 | | 7y=5.6 | | -3(2x+1)-6=15 | | 4x-1(3x-1)=2 | | 13+8x=-75 | | 5^(2x)+1=26(5^(x-1)) | | 2(3x+1=128 | | 12u=u+22 | | -89=16-5x | | 2z+90=19z+39 | | 7x^2-84x+245=0 | | x^2−7x-18=0 | | 3/112=a/14 | | -4x-9=51 | | 5a+7=3a+9 | | 88=x/9+13 | | x/24+3=8 | | 2r^2+6r-80=0 |

Equations solver categories